SWOT Analysis Training for SMEs in Serang, Banten Province - Rodhiah, Rodhiah; Thera, Jufin; Ajuanda, Tania Imeylia; Talaar, Timothy Elmore (CV. Proaksara Global Transeduka, 2025)
Competitive advantage is one of the important things that all entrepreneurs have in various fields. Currently, more and more competitors are present in the market, making entrepreneurs inevitably have to increase their competitiveness, in order to remain superior to competitors. The way to achieve this can be done through SWOT analysis, where this method is used by entrepreneurs to find out what factors need more attention or even unconsciously missed. The main objective of the PKM activity is to increase competitive advantage by adding partner knowledge about SWOT (Strength, Weakness, Opportunity, and Threat). The partners targeted by the training team from the Faculty of Economics and Business, Tarumanagara University are creative product businesses located in Serang Banten. The activity material was presented in the form of PPT. The activity was carried out using the online training method through Zoom, assisted by 3 students. It is expected that after the training, partners are able to identify SWOT in their business so that they can increase their advantage over competitors from competitors.